Application of Evaluation Model to Analyze the Implementation of Clean and Healthy Life Behavior Program on Practice Subject of Culinary Arts Program - Sholihah, Muflihatus; Purnawirawan, Okta; Puspita, Chintya Paramita (Universitas Negeri Semarang, 2020)
Clean and Healthy Life BehaviorÃ‚Â is one of the suitable programs to be applied to the school in realizing healthy cultured schools. Ibu Kartini Vocational High School, Semarang which has a Culinary Arts Program has certainly implemented the Clean And Healthy Life Behavior program in Teaching and Learning Activities (KBM). One of the applications of the Clean And Healthy Life Behavior program in the KBM is in Practice Subject of Culinary Arts Program, which certainly needs to be evaluated. CIPP Evaluation Model is one of the models that can be applied. The CIPP evaluation model emphasizes the aspect of evaluation in terms of context, input, process and product of a program of activities. The purpose of this study is to analyze the implementation of the Clean And Healthy Life Behavior program in the Practice Subject of Culinary Arts Program from the aspect of evaluating context, input, process, and product. The results of the implementation of the Clean And Healthy Life Behavior program are among others applied to: (1) Hygiene and Sanitation Work Areas; (2) Personal Hygiene Food Handlers / Students; and (3) Occupational Safety Health in the Laboratory / Kitchen Environment. The level of achievement in hygiene sanitation in the kitchen of the Culinary Arts ProgramÃ‚Â Ibu Kartini Vocational High School in Semarang has